Strengthening Interest and Riba in Bank Financial Institutions - Sofhian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
This research examines and substantially analyzes the problem of riba from a rational perspective, and at the end of this paper offers a profit-sharing system and profit-sharing system as an alternative solution to the interest system in the transaction system in banks (bank financial institutions). Interest in the study of riba has always been a topic that does not experience saturation and is still very hotly discussed in Islamic economics. This can be seen from the discussion of riba which has always colored the discourse of Muslim thought and debates that have barely found common ground. The results of the study display that the debate on thoughts about riba and bank interest shows that the issue of riba is very closely related to muamalah (economy) issues, especially those that occur in Bank financial institutions. The concept of riba turning into interest cannot be separated from the evaluation of the development of these financial institutions.